Effect of Zn content on corrosion behavior of Mg-Y-Zn alloys - Shi Y.; Liu X.-Q.; Liu Z.-L.; Xie H.-J.; Wang Y.-H.; Li J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The microstructure, corrosion behavior, and electrochemical behavior of as-cast Mg-4Y-xZn (x=1,2,3,4 wt.%) are studied by SEM, weight loss and electrochemical tests. Mg12YZn (X), Mg3Y2Zn3 (W) and Mg24Y5 constitute the phase composition system of the alloy. When Zn content is 1 wt.%, all tests reveal that alloy has the optimal corrosion performance. The second phase in these alloys, due to their nobler nature than α-Mg, exists as a cathode during the corrosion process, so that α-Mg preferentially occurs corrosion to accelerate the formation of corrosion pits. After soaking in 3.5 wt.% NaCl solution for some time, the stability of the W phase changed, and gradually dissolved, which was finally removed by chromic acid used for removal of corrosion products. In addition, X phase can be used as an anode in the micro-galvanic cells formed with W phase to reduce the corrosion rate of α-Mg and thus improve the corrosion performance of the alloy.